Role of inter-species recombination of the ftsI gene in the dissemination of altered penicillin-binding-protein-3-mediated resistance in Haemophilus influenzae and Haemophilus haemolyticus - Witherden, E.A. (2014)
Objectives: To screen the ftsI gene sequences obtained from clinical isolates of non-typeable H. influenzae (NTHi), and Haemophilus haemolyticus for the presence of mosaic ftsI gene structures, and to evaluate the role homologous recombination of the ftsI gene has on the formation and distribution of resistant ftsI genes in NTHi. Methods: The ftsI genes of 100 Haemophilus isolates comprising genetically defined β-lactamase-negative ampicillin-susceptible (gBLNAS) and β-lactamase-negative ampicillin-resistant (gBLNAR) isolates of NTHi (n=50) and H. haemolyticus (n=50) were analyzed in this study. The full-length ftsI gene sequences of all study isolates were screened for mosaic ftsI gene structures using H. influenzae Rd and H. haemolyticus ATCC 33390 as reference parental sequences, and were subjected to recombination analysis using bioinformatics software Mega5 and Simplot. Results: Of the 100 clinical isolates analyzed 34% (34/100) harbored mosaic ftsI gene structures containing distinct ftsI gene fragments similar to both reference parental sequences. Inter-species recombination events were predominantly encountered in the ftsI gene of gBLNAR isolates of NTHi and H. haemolyticus, and were always associated with the formation of a mosaic fragment at the 3’ end of the ftsI gene. There was no evidence supporting the horizontal gene transfer (HGT) of the entire ftsI gene among the clinical isolates in vivo. Conclusion: We provide evidence for the HGT and inter-species recombination of the ftsI gene among isolates of NTHi and H. haemolyticus in a clinical setting, highlighting the importance recombination of the ftsI gene has on the emergence of altered PBP3s and BLNAR mediated resistance.